Zwitterion Coordination Induced Highly Orientational Order of CH3NH3PbI3 Perovskite Film Delivers a High Open Circuit Voltage Exceeding 1.2 V - Zhou, Weiran; Li, Dan; Xiao, Zhengguo; Wen, Zhilin; Zhang, Mengmeng; Hu, Wanpei; Wu, Xiaojun; Wang, Mingtai; Zhang, Wen‐Hua; Lu, Yalin; Yang, Shihe; Yang, Shangfeng (Advanced functional materials, 2019)
The organic–inorganic halide CH3NH3PbI3 (MAPbI3) has been the most commonly used light absorber layer of perovskite solar cells (PSCs); however, solution‐processed MAPbI3 films usually suffer from random crystal orientation and high trap density, resulting in inferior power conversion efficiency (PCE) with open circuit voltage (Voc) being typically below 1.2 V for PSC devices. Herein, for the first time an imidazole sulfonate zwitterion, 4‐(1H‐imidazol‐3‐ium‐3‐yl)butane‐1‐sulfonate (IMS), is applied as a bifunctional additive in regular‐structure planar heterojunction PSC devices to regulate the crystal orientation, yielding highly ordered MAPbI3 film and passivating the trap states of the film. Such a dual effect of IMS is fulfilled via coordination interactions between the sulfonate moiety of IMS with the Pb2+ ion and the electrostatic interaction between the imidazole of IMS with the I– ion of MAPbI3. As a result, under a optimized IMS doping ratio of 0.5 wt%, the PSC device exhibits a significant increase in PCE from 18.77% to 20.84%, with suppressed current–voltage hysteresis and promoted ambient stability. Moreover, a high Voc of 1.208 V is achieved under a higher IMS doping ratio of 1.2 wt%, which is the highest Voc for regular‐structure MAPbI3 planar PSC devices based on TiO2 electron transport layer. A bifunctional zwitterion additive affords efficiency enhancement of perovskite solar cells: an imidazole sulfonate zwitterion is doped into a CH3NH3PbI3 precursor solution as a bifunctional additive, enabling regulation of crystalline grain orientation and passivation of trap states. As a result, a significant efficiency enhancement and a high open circuit voltage (Voc) of 1.208 V are achieved.